Trait Sensitivity to Negative and Positive Feedback Does Not Interact With the Effects of Acute Antidepressant Treatment on Hedonic Status in Rats - Surowka, Paulina; Noworyta, Karolina; Rygula, Rafal (Frontiers in Behavioral Neuroscience, 2020)
Aberrant cognition plays a pivotal role in the development and maintenance of depression. One of the most important cognitive distortions associated with depression is aberrant sensitivity to performance feedback. Under clinical conditions, this sensitivity can be measured using the probabilistic reversal learning (PRL) test, which has also been recently implemented in animal studies. Although the evidence for the coexistence of depression and altered feedback sensitivity is relatively coherent, it is unclear whether this sensitivity can influence the effectiveness of antidepressant treatment. In the present research, we investigated how trait sensitivity to negative and positive feedback interacts with the effects of acute antidepressant treatment on hedonic status in rats. We tested a cohort of rats with a series of 10 PRL tests, and based on this screening, we classified each animal as sensitive or insensitive to negative and positive feedback. Subsequently, in the Latin square design, we evaluated the effects of a single administration of 2 antidepressant drugs (each at 3 different doses: agomelatine: 5, 10, and 40 mg/kg; mirtazapine 0.5, 1, and 3 mg/kg) on the hedonic status of rats in the sucrose preference tests. There was no statistically significant interaction between trait sensitivity to feedback and the effects of acute antidepressant treatment on hedonic status in rats.